PADC nuclear track detector for ion spectroscopy in laser-plasma acceleration. (August 2020) - Seimetz, M.; Peñas, J.; Llerena, J.J.; Benlliure, J.; García López, J.; Millán-Callado, M.A.; Benlloch, J.M.
Highlights: First experimental data for new type of PADC, Radosys RS39. Low sensitivity to protons (0–3 MeV) due to high LET threshold. High sensitivity to carbon ions (0–12 MeV) in agreement with other types of PADC. Highly suitable for discrimination between different ion species. Nuclear track material for laser-ion acceleration and biomedical research. Abstract: The transparent polymer polyallyl-diglycol-carbonate (PADC), also known as CR-39, is widely used as detector for heavy charged particles at low fluence. It allows for detection of single protons and ions via formation of microscopic tracks after etching in NaOH or KOH solutions. PADC combines a high sensitivity and high specificity with inertness towards electromagnetic noise. Present fields of application include laser-ion acceleration, inertial confinement fusion, radiobiological studies with cell cultures, and dosimetry of nuclear fragments in particle therapy. These require precise knowledge of the energy-dependent response of PADC to different ion species. We present calibration data for a new type of detector material, Radosys RS39, to protons (0.2–3 MeV) and carbon ions (0.6–12 MeV). RS39 is less sensitive to protons than other types of PADC. Its response to carbon ions, however, is similar to other materials. Our data indicate that RS39 allows for measuring carbon ion energies up to 10 MeV only from the track diameters. In addition, it can be used for discrimination between protons and carbon ions in a single etching process.